Different Influences of Bacterial Communities on Fe (III) Reduction and Phosphorus Availability in Sediments of the Cyanobacteria- and Macrophyte-Dominated Zones - Fan, Xianfang; Ding, Shiming; Gong, Mengdan; Chen, Musong; Gao, ShuaiShuai; Jin, Zengfeng; Tsang, Daniel C. W. (Frontiers in Microbiology, 2018)
Little is known about the effects of the bacterial community on the iron and phosphorus cycles in sediments across different primary producer-dominated ecosystems in different seasons. Lake Taihu provides a suitable study area by having cyanobacteria- and macrophyte-dominated zones co-occurring in one lake. The abundance and composition of bacterial community was investigated using qPCR and 16S rRNA gene amplicon high throughput sequencing, respectively. Compared with sediments in the cyanobacteria-dominated zone, sediments in the macrophyte-dominated zone had higher TP, TOC and TN contents but lower DO and Eh values. The soluble reactive P (SRP), soluble Fe, and their molar ratio (Fe/P) were lower in the cyanobacteria-dominated sediment than those in the macrophyte-dominated sediment. Consistent with this was the significantly lower abundance of total and typical Fe redox transforming bacteria in the cyanobacteria-dominated sediment than those in the macrophyte-dominated sediment. Correlation analyses also revealed positive influence of abundances of total bacteria and typical Fe reducing bacteria on soluble Fe and Fe/P ratio. Our results showed that, in the cyanobacteria-dominated open water zone, Acidimicrobiaceae was capable of Fe metabolism, contributing to the higher P flux in summer. In typical cyanobacteria-dominated bay, Sva0081 sediment group and Desulfobulbaceae could transform sulfate to sulfide which then cause the reduction of Fe(III), while in macrophyte-dominated zones, Clostridium sensu stricto 1 could couple oxidation of organic carbon with the reduction of Fe (III). The present study contributes new knowledge linking the bacterial communities with the physicochemical cycles of Fe and P in sediments under different primary producer habitats.